3D bioprinting of high-performance hydrogel with in-situ birth of stem cell spheroids - Shunyao Zhu; Xueyuan Liao; Yue Xu; Nazi Zhou; Yingzi Pan; Jinlin Song; Taijing Zheng; Lin Zhang; Liyun Bai; Yu Wang; Xia Zhou; Maling Gou; et al. (Bioactive Materials)
Digital light processing (DLP)-based bioprinting technology holds immense promise for the advancement of hydrogel constructs in biomedical applications. However, creating high-performance hydrogel constructs with this method is still a challenge, as it requires balancing the physicochemical properties of the matrix while also retaining the cellular activity of the encapsulated cells. Herein, we propose a facile and practical strategy for the 3D bioprinting of high-performance hydrogel constructs through the in-situ birth of stem cell spheroids. The strategy is achieved by loading the cell/dextran microdroplets within gelatin methacryloyl (GelMA) emulsion, where dextran functions as a decoy to capture and aggregate the cells for bioprinting while GelMA enables the mechanical support without losing the structural complexity and fidelity. Post-bioprinting, the leaching of dextran results in a smooth curved surface that promotes in-situ birth of spheroids within hydrogel constructs. This process significant enhances differentiation potential of encapsulated stem cells. As a proof-of-concept, we encapsulate dental pulp stem cells (DPSCs) within hydrogel constructs, showcasing their regenerative capabilities in dentin and neovascular-like structures in vivo. The strategy in our study enables high-performance hydrogel tissue construct fabrication with DLP-based bioprinting, which is anticipated to pave a promising way for diverse biomedical applications.